2006
DOI: 10.1103/physrevd.73.124028
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid approach to black hole perturbations from extended matter sources

Abstract: We present a new method for the calculation of black hole perturbations induced by extended sources in which the solution of the nonlinear hydrodynamics equations is coupled to a perturbative method based on Regge-Wheeler/Zerilli and Bardeen-Press-Teukolsky equations when these are solved in the frequency domain. In contrast to alternative methods in the time domain which may be unstable for rotating black hole spacetimes, this approach is expected to be stable as long as an accurate evolution of the matter so… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 32 publications
0
12
1
Order By: Relevance
“…Although more sophisticated approaches involving perturbative techniques around black holes can be employed to study the gravitational‐wave emission from these tori (Nagar et al 2005; Ferrari, Gualtieri & Rezzolla 2006; Nagar et al 2007), we here resort to the simpler and less expensive use of the Newtonian quadrupole approximation (Zanotti et al 2003), which has been suitably modified to account for the presence of a magnetic field, as done by Kotake et al (2004). In particular, the quadrupole wave amplitude A E2 20 , which is the second time derivative of the mass‐quadrupole moment, is computed through the ‘stress formula’ (Obergaulinger et al 2006) …”
Section: Resultsmentioning
confidence: 99%
“…Although more sophisticated approaches involving perturbative techniques around black holes can be employed to study the gravitational‐wave emission from these tori (Nagar et al 2005; Ferrari, Gualtieri & Rezzolla 2006; Nagar et al 2007), we here resort to the simpler and less expensive use of the Newtonian quadrupole approximation (Zanotti et al 2003), which has been suitably modified to account for the presence of a magnetic field, as done by Kotake et al (2004). In particular, the quadrupole wave amplitude A E2 20 , which is the second time derivative of the mass‐quadrupole moment, is computed through the ‘stress formula’ (Obergaulinger et al 2006) …”
Section: Resultsmentioning
confidence: 99%
“…QNMs excitation has also been shown to give a strong contribution to the signal emitted after the core collapse of a rotating NS to a Kerr black hole [58]. Moreover, in [59,60] the gravitational emission of a black hole perturbed by a thick, oscillating accretion disk has been studied; in a subsequent paper [61] it has been shown that if the disk is extremely dense, black hole oscillations can be excited, even though, due to the symmetry of the source, only by a small amount. All numerical simulations of astrophysical processes in which QNMs are excited show that the leading contribution belong to the lowest frequency, = 2 mode.…”
Section: The Quasi-normal Modes Of a Kerr Black Holementioning
confidence: 96%
“…Quasi-normal modes excitation has also been shown to give a strong contribution to the signal emitted after the core collapse of a rotating neutron star to a Kerr black hole [38]. Moreover, in [39] the gravitational emission of a black hole perturbed by a thick, oscillating accretion disk has been studied; in a subsequent paper [40] it has been shown that if the disk is extremely dense, black hole oscillations can be excited, even though, due to the symmetry of the source, only by a small amount. All numerical simulations of astrophysical processes in which QNMs are excited show that the leading contribution belong to the lowest frequency, ℓ = 2 mode.…”
Section: Excitation Of Black Hole Quasi-normal Modesmentioning
confidence: 99%